Yellow fever in Piura. Brief observations about their nature - Zapata, Carlos Enrique (1920)
Little while now, one of the richest areas of the country, the department of Piura, is being cruelly whipped by the most terrible epidemics: bubonic plague, typhoid, malaria, etc., which has been to join since last year yellow yellow fever. These abnormal conditions being experienced by the department of Piura and serious projections that has had, and now has, the epidemic that I deal with, are an inevitable and fatal to the inhabitants of that region hazard and therefore an insurmountable obstacle to increasing population as well as the development of trade and wealth.